Degree of Satisfaction with the Training Programs through E-platforms in Developing Self-skills and Training through them among Taibah University Students - AL- Ansary, Rofaydah Adnan (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the satisfaction level with training programs via electronic platforms in the development of self- development skills and training for Taibah University students. The researcher has designed a questionnaire as the main tool of the study and intended to measure the degree of satisfaction about the training programs provided by electronic platforms on self- development skills and training via it. The population of the current study was all the female students who study the university like skills course, while the sample of the study consisted of 125 students who were selected randomly in the second semester of the academic year 1439/1440. A number of statistical methods have been used to reach the findings such as frequencies, means and standard deviation. The study adopted a descriptive approach.The results of the study showed that the satisfaction rate of the study sample on the role of training programs through electronic platforms in the development of self- development skills and training through them was very high, with means scores (4.3). Findings of the study revealed that there were statistically significant differences could be attributed to scientific major variable. In contrast, there were no statically significant differences that could be ascribed to students' cumulative grades. It was found that the most appropriate training programs from the point of view of the study sample were self-development skill followed by education, then economics and management. The study has concluded with many recommendations; the most important one was to increase awareness of the importance of the available training programs via e- platforms which provide plenty of knowledge to develop aptitudes and skills. The study also provided a number of suggestions.
Keywords: educational techniques; training programs; e- training; e- platforms